2012
DOI: 10.1042/cs20120167
|View full text |Cite
|
Sign up to set email alerts
|

Role of GLP-1 and DPP-4 in diabetic nephropathy and cardiovascular disease

Abstract: Although there have been major advances in the understanding of the molecular mechanisms that contribute to the development of diabetic nephropathy, current best practice still leaves a significant treatment gap. The incidence of diabetes and associated nephropathy is increasing, with the main cause of mortality being related to cardiovascular causes. Novel therapies which are both 'cardio-renal'-protective seem the logical way forward. In the present review, we discuss the GLP-1 (glucagon-like peptide-1) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 99 publications
2
47
0
4
Order By: Relevance
“…Several reports suggest that DPP-4 inhibitors have antiinflammatory effects and can improve bone marrow function [45,46]. The possibility of scission protection by DPP-4 with antiinflammatory agents such as BNP/ANP (brain natriuretic peptide/atrial natriuretic peptide) or NPY (neuropeptide), which are substrates of DPP-4, is suggested, and an intracorporeal inflammation condition is therefore thought to be ameliorated by DPP-4 inhibitor [47][48][49][50]. This may explain the improved iron bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest that DPP-4 inhibitors have antiinflammatory effects and can improve bone marrow function [45,46]. The possibility of scission protection by DPP-4 with antiinflammatory agents such as BNP/ANP (brain natriuretic peptide/atrial natriuretic peptide) or NPY (neuropeptide), which are substrates of DPP-4, is suggested, and an intracorporeal inflammation condition is therefore thought to be ameliorated by DPP-4 inhibitor [47][48][49][50]. This may explain the improved iron bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Among the recently launched diabetes drugs that have achieved marked progress in treatment, oral dipeptidyl peptidase-4 (DPP-4) inhibitors ("DPP-4 inhibitors") carry a lower risk of hypoglycemia and body weight gain (13)(14)(15)(16)(17). Their benefits in protecting the kidneys have been also reported in recent studies (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 91%
“…Liraglutide (3 mg) has been already approved as a general obesity therapy by FDA and EMA. Exenatide has been studied in a number of defined phenotypes of obesity such as Prader-Willi syndrome, hypothalamic obesity, pediatric obesity, olanzapine-induced obesity, and polycystic ovary syndrome [30,31]. GLP-1 RA may also have a role in pre-diabetes, as the proportion of patients with pre-diabetes decreased by 52% following 2 years of treatment with liraglutide in the obesity trial [32].…”
Section: Other Indications For Incretin Therapies Obesitymentioning
confidence: 99%